POTENTIAL OF ASSET SECURITISATION IN SINGAPORE - Chong, Joanne Lee Men (2008)
This dissertation aims to study the potential of Asset Securitisation in Singapore. Three main securitisation vehicles have been used by Singaporeâs property companies to divest real estate assets, namely, mortgage-backed bond (MBB), asset-backed securitisation (ABS) and real estate investment trust (REIT). The focus of this paper is on real estate securitisation (RES) taking into consideration of commercial mortgage-backed securitisation (CMBS), residential mortgage-backed securitisation (RMBS) and real estate investment trust (REIT) in Singapore. This paper provided an overview of the concept of asset securitisation; followed by a critical analysis of the importance of asset securitisation and the different channels available in Singapore. It also examines some of the impediments and impetus to the recent development of REIT in Singapore, and finally, my opinion on the development of RES in Singapore as part of the conclusion.